Preclinical study of experimental burns treated with photobiomodulation and Human Amniotic Membrane, both isolated and associated - Fernanda Cláudia Miranda Amorim; Emilia Ângela Loschiavo Arisawa; Luciana Barros Sant’anna; Ana Beatriz Mendes Rodrigues; Davidson Ribeiro Costa (Revista Latino-Americana de Enfermagem, 2023)
Abstract Objective: to evaluate the effect of photobiomodulation with low-level 660 nm laser alone or associated with Human Amniotic Membrane in the repair of partial-thickness burns in rats. Method: an experimental study conducted with 48 male Wistar rats, randomized into four groups: Control, Human Amniotic Membrane, Low-Level Laser Therapy, and Low-Level Laser Therapy associated with Human Amniotic Membrane. The histopathological characteristics of the skin samples were analyzed 7 and 14 days after the burn. The data obtained were submitted to the Kolmogorov-Smirnov and Mann-Whitney tests. Results: the histological analysis of the burn injuries showed a decrease in inflammation (p<0.0001) and an increase in proliferation of fibroblasts (p<0.0001) mainly at 7 days in all treatments related to the control group. At 14 days, the greater effectiveness in accelerating the healing process was significant (p<0.0001) in the Low-Level Laser Therapy group associated with the Human Amniotic Membrane. Conclusion: the association of photobiomodulation therapies with the Human Amniotic Membrane allowed verifying a reduction in the healing process time of the experimental lesions, stimulating its proposal as a treatment protocol in partial-thickness burns.